Evaluation of monkey intraocular pressure by rebound tonometer - Yu, Wenhan (Molecular Vision, 2009)
PURPOSE: To evaluate the usefulness of the TonoVet™ rebound tonometer in measuring intraocular pressure (IOP) of monkeys. METHODS: The accuracy of the TonoVet™ rebound tonometer was determined in cannulated eyes of anesthetized rhesus monkeys where IOP was controlled by adjusting the height of a connected perfusate reservoir. To assess the applicability of the equipment through in vivo studies, the diurnal fluctuation of IOP and effects of IOP-lowering compounds were evaluated in monkeys. RESULTS: IOP readings generated by the TonoVet™ tonometer correlated very well with the actual pressure in the cannulated monkey eye. The linear correlation had a slope of 0.922±0.014 (mean±SEM, n=4), a y-intercept of 3.04±0.61, and a correlation coefficient of r(2)=0.97. Using this method, diurnal IOP fluctuation of the rhesus monkey was demonstrated. The tonometer was also able to detect IOP changes induced by pharmacologically active compounds. A single topical ocular instillation (15 μg) of the rho kinase inhibitor, H1152, produced a 5–6 mmHg reduction (p<0.001) in IOP, lasting at least 4 h. In addition, topical administration of Travatan®, a prostaglandin agonist, induced a small transient IOP increase (1.1 mmHg versus vehicle control; p=0.26) at 2 h after treatment followed by a pressure reduction at 23 h (−2.4 mmHg; p<0.05). Multiple daily dosing with the drug produced a persistent IOP-lowering effect. Three consecutive days of Travatan treatment produced ocular hypotension of −2.0 to −2.2 mmHg (p<0.05) the following day. CONCLUSIONS: The rebound tonometer was easy to use and accurately measured IOP in the rhesus monkey eye.